Gender, class, and paradoxical mobilities of Thai marriage migrants in Austria - Butratana, Kosita; Trupp, Alexander * (Wiley, 2021)
In this paper, we investigate whether marriage‐related migration promotes socioeconomic mobility and how class belonging and educational background affects Thai women's migration experience and socioeconomic mobility. Drawing on qualitative interviews, supported by a questionnaire survey with Thai women living in Austria and who are in a relationship with a Western male citizen, we seek to dismantle simplistic notions about hypergamy and question common assumption about marrying up or down in migration contexts. We compare socioeconomic indicators such as formal education, occupation, and income before and after the migration and analyse migrants’ experiences in Austria. The results show a complex picture of upward and downward socioeconomic mobilities. Two distinct scenarios of paradoxical mobilities have been identified. On the one hand, some migrants feel empowered (when experiencing economic downward mobility) as they enjoy the freedom of living in Austria, while on the other hand, those migrants experiencing upward mobility feel a loss of their personal autonomy.